Do South African mothers shake their babies? incidence and risk factors for infant abuse in Cape Town - Nefdt, Kirsten C (Department of Psychology, 2020)
Abusive head trauma from shaking is a recognised common cause of fatal head injury in young children globally, although there is little evidence of its occurrence in South Africa. This is perplexing given that the country has amongst the highest reported under-five child mortality and infanticide rates worldwide. To determine whether infants under one-year are violently shaken, a cross-sectional study was conducted with 385 mothers and other primary female caregivers (ages 18 to 60 years; mean age = 27 years) from three high-risk communities in Cape Town. Semi-structured interviews were used to examine: (1) the incidence of shaking, (2) the triggers for shaking, (3) the risk factors for shaking, thoughts of shaking, and knowledge of the dangers of shaking, and (4) the methods used to console crying infants. Results showed that 13.2% (n = 51) of all participants self-reported violent shaking, and 20% (n = 77) had thoughts of shaking their infants. Following a content analysis, three primary triggers for shaking were identified, these were: inconsolable infant crying, feeling angry or frustrated, and being stressed. Findings from a thematic analysis also showed that shaking occurred during a momentary loss of control, and participants seemed to have limited support at the time. The results from three hierarchical logistic regression analyses showed that (1) alcohol use, infant age, a lower knowledge of the dangers of shaking, inconsolable crying, and having thoughts of shaking, predicted shaking, (2) caregiver age, infant age, knowledge of the dangers of shaking, and caregiver responses to infant crying, predicted having thoughts of shaking, and (3) social support, caregiver history of childhood abuse, and having thoughts of shaking, predicted knowledge of the dangers of shaking. Finally, a content analysis revealed three protective factors for infant crying, these were: (1) having easy, contented children, (2) not feeling stressed in response to infant crying, and (3) leaving an infant alone to self-soothe. Taken together, the current findings have programmatic implications that may help prevent the violent shaking of young children in South Africa.